PENGARUH BUDAYA ORGANISASI, MOTIVASI KERJA DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR TERHADAP KINERJA PEGAWAI PEMERINTAH KABUPATEN PAMEKASAN - - Muzakki; Muhammad Alkirom Wildan; Helmi Buyung Aulia Safrizal (Kompetensi (Competence : Journal of Management Studies), 2017)
The purpose of this research is to examine and analyze the influence of organizational culture, work motivation and organizational citizenship behavior (OCB) to employee performance. This research is conducted in Pamekasan Regency Government. The samples of this research are 116 respondents. The sample technique which used in this research is proportional stratified random sampling. And then, this study employs questionnaire by a large number of answers based on a 5-point likert scale to collect the needed data and information.  The result of this research reveals that the work motivation and organizational citizenship behavior (OCB) influence significantly to employee performance in Pamekasan Regency Government. Nevertheless, organizational culture do not influence significantly to employee performance in Pamekasan Regency Government.